2021
DOI: 10.1177/02601060211020975
|View full text |Cite
|
Sign up to set email alerts
|

Examining the associations between a posteriori dietary patterns and obesity indexes: Systematic review of observational studies

Abstract: Background: Few reports on the association of population-derived dietary patterns with excess body weight, using the approach of a systematic review currently exist. Aim: The aim of the present systematic review was to identify dietary patterns associated with body mass index (BMI), body weight (BW)/BMI change, weight status and weight loss maintenance status. Methods: Using MEDLINE (via PubMed) and EBSCO Host databases, we systematically reviewed studies from 1980 to 2020, which included men and women, aged ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In other studies of person-centered DP approaches, a "processed" or "Western" DP has been followed by 20% [36] to over a third of subjects [25,37], whereas "prudent" or "healthier" DPs tend to be followed by 20% of the population [25,36,37]. In general, the investigation of DPs in other adults and the elderly result in patterns usually named "traditional", which reflects the most common DP of the population, "unhealthy", which includes a high consumption of meats and an energy-dense-nutrient-poor diet, and "healthy", which has a high intake of fruits and vegetables [38]. In the present study, the DP that could correspond with this last point was named "Diet concerns", once its followers demonstrated some common dietary restrictions of people dieting (less pasta, tubers and beans), with a greater consumption of UPF popularly regarded as healthy, such as crackers and ultra-processed yoghurts, which can reflect the pervasive presence of nutrition and health claims in many UPF packages [39].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies of person-centered DP approaches, a "processed" or "Western" DP has been followed by 20% [36] to over a third of subjects [25,37], whereas "prudent" or "healthier" DPs tend to be followed by 20% of the population [25,36,37]. In general, the investigation of DPs in other adults and the elderly result in patterns usually named "traditional", which reflects the most common DP of the population, "unhealthy", which includes a high consumption of meats and an energy-dense-nutrient-poor diet, and "healthy", which has a high intake of fruits and vegetables [38]. In the present study, the DP that could correspond with this last point was named "Diet concerns", once its followers demonstrated some common dietary restrictions of people dieting (less pasta, tubers and beans), with a greater consumption of UPF popularly regarded as healthy, such as crackers and ultra-processed yoghurts, which can reflect the pervasive presence of nutrition and health claims in many UPF packages [39].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we found that increased diet quality, and specifically, higher MTD adherence, can offer improvements for body weight in the long term, independently of energy intake and other confounding factors. Recently, in a systematic review by Koutras et al [ 65 ], it was found that a healthy dietary pattern, similar to an MTD (i.e., high intake of whole grains, fruits and vegetables, unprocessed cereals, and dairy, and low intake of sweets and high-fat foods), was related to longitudinal changes in body weight status (assessed as body weight or BMI) and overweight/obesity risk, which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based diets may be useful for the prevention of weight gain and control of body weight [29,30]. For instance, vegetarians showed a lower body weight compared to non-vegetarians in cross-sectional studies [31,32].…”
Section: Effect Of Plant-based Diets On Body Weight Control and Obesitymentioning
confidence: 99%